Implementasi Problem Based Learning Mata Pelajaran Pendidikan Agama Islam dalam Meningkatkan Prestasi Belajar Siswa Di SD NU Nurul Ishlah Gresik - Nailil Hikmiyah; Fany Hardian Febriansyah; Nanang Achmadi; Tri Marfiyanto (LPPM STAI Ihyaul Ulum Gresik, 2023)
Starting from a phenomenon of the learning process in schools, in the process many teachers still find their role as the center of learning activities or teacher centered. Meanwhile, in essence, those who play an active role are students or student centered. Of the various existing learning models and strategies, problem based learning is one option that can accommodate improving student achievement. Researchers chose problem based learning because the learning process is based on real life problems. In implementing this learning, students are formed into groups and invited to discuss together.The theoretical framework in this research uses cognitive theory while the research method used is descriptive qualitative field research with a phenomenological approach.The research results are the author's findings in the field as well as the answer to the problem formulation. First, the implementation of problem based learning in Islamic religious education subjects in improving student learning achievement at NU Nurul Ishlah Elementary School has been successful although there is still something that needs to be developed. Second, the implications of problem based learning in Islamic religious education subjects at SD NU Nurul Ishlah Gresik include: students are able to develop independence, and students experience an increase in learning achievement scores. The three supporting factors in implementing problem based learning in Islamic religious education subjects are teachers, students, facilities and the environment. And the inhibiting factors are: Lack of lesson hours for Islamic religious education subjects and factors of the students' parents.